Beyond Access: Exploring the Dimensions of Digital Inequality among English Education Students in Islamic Higher Education - Eka Mayasari; Mutiara Yulia Effendi (Lembaga Pengembangan Kinerja Dosen, 2024)
The integration of digital technology in higher education has significantly reshaped learning practices and academic engagement. However, the benefits of digital transformation are not evenly distributed among students, leading to persistent inequalities known as the digital divide. This study explores the dimensions and determinants of digital inequality among Tadris Bahasa Inggris (English Education) students at the Islamic Institute of Miftahul Ulum Tanjungpinang. Using a qualitative case study approach, data were collected through observations, semi-structured interviews, and document analysis involving 15 undergraduate students. The findings reveal that while students have sufficient access to digital devices and the Internet, disparities exist in digital literacy, motivation, and the quality of technology use. Five main factors contribute to the digital divide: differences in digital competence, psychological barriers, limited institutional support, unequal technological engagement, and overreliance on artificial intelligence. These findings confirm that digital inequality has shifted from physical access to differences in digital engagement and benefits, aligning with Van Dijk’s (2005) multidimensional model. The study emphasizes the need for comprehensive digital literacy programs, curriculum integration of technology, and supportive institutional policies to foster equitable digital learning environments. Theoretically, this research extends the discussion on the second-level digital divide within the context of English language education in Islamic higher education, offering insights for developing inclusive and technology-enhanced pedagogical practices.